2021
DOI: 10.3390/en14217010
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Programming and Solution Approaches for Transportation Optimisation in Supply Network

Abstract: The problem of transport is a special type of mathematical programming designed to search for the optimal distribution network, taking into account the set of suppliers and the set of recipients. This article proposes an innovative approach to solving the transportation problem and devises source codes in GNU Octave (version 3.4.3) to avoid the necessity of carrying out enormous calculations in traditional methods and to minimize transportation costs, fuel consumption, and CO2 emission. The paper presents a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In [12] it was proposed to use the Vogel's approximation method to determine the reference plan. The advantage of [12] is the ability to obtain either a reference plan close to optimal, or the optimal plan itself. The disadvantage [12] is the high computational costs.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12] it was proposed to use the Vogel's approximation method to determine the reference plan. The advantage of [12] is the ability to obtain either a reference plan close to optimal, or the optimal plan itself. The disadvantage [12] is the high computational costs.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The advantage of [12] is the ability to obtain either a reference plan close to optimal, or the optimal plan itself. The disadvantage [12] is the high computational costs.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The calculation of the energy performance of a building is only accurate if the tightness of the building is measured [28,29]. It can be measured by various methods: theoretically [30,31], empirically [32][33][34][35][36], or by single-component models [37]. Relander et al tested the tightness of connections between the basement wall and the wall with a wooden structure.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…They naturally position the possibilities of improving the areas requiring improvement. The issues of optimization are located in the area of linear programming [1][2][3], where the end result is the achievement of the assumed optimization goal. In practice, the assumed function of the objective may therefore be differently defined, for example, to strive to achieve a certain extreme in the form of minimizing inputs or maximizing profits.…”
Section: Introductionmentioning
confidence: 99%
“…The results of calculations for 50 possible scenarios related to two types of vehicles i.e., with a capacity of 4500.0 (dm 3 ) and with a capacity of 7500.0 (dm 3 ) are presented in Figures 4 and 5, respectively. Summing up the results obtained for all 50 considered scenarios of the planne flight schedule (Figure 3) and all flight times and frequencies of takeoffs, we concluded that:…”
mentioning
confidence: 99%